2008
DOI: 10.1007/s00414-008-0229-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of bacterial degradation of ethyl glucuronide and ethyl sulphate

Abstract: Recent studies show that ethyl glucuronide (EtG) can be decomposed by bacteria; whilst so far no degradation of ethyl sulphate (EtS) has been observed. In the present study, in vitro experiments with bacterial colonies were performed. Bacteria (Escherichia coli, Klebsiella pneumoniae, Clostridium sordellii) were isolated from autopsy material (liver, heart blood, urine, ascites, pericardial fluid, pleural fluid) tested for beta-glucuronidase activity, and three bacterial strains were added to nutrient-deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 20 publications
3
61
0
7
Order By: Relevance
“…Nine of these ethanol positive cases were negative for EtG in both blood and urine. We cannot totally exclude the possibility that they were false negatives caused by degradation in both media, but the analysis of EtS could answer this question, as recent research has found superior stability of EtS (119,(146)(147)(148). The analyses of EtS showed that total loss of EtG also in urine probably did not occur, because we found that none of the nine urine samples negative for EtG contained EtS.…”
Section: Post Mortem Presence Of Etgmentioning
confidence: 73%
“…Nine of these ethanol positive cases were negative for EtG in both blood and urine. We cannot totally exclude the possibility that they were false negatives caused by degradation in both media, but the analysis of EtS could answer this question, as recent research has found superior stability of EtS (119,(146)(147)(148). The analyses of EtS showed that total loss of EtG also in urine probably did not occur, because we found that none of the nine urine samples negative for EtG contained EtS.…”
Section: Post Mortem Presence Of Etgmentioning
confidence: 73%
“…Another study has also shown that EtG levels were concordant with alcohol intake habits [15]. However, it has been suggested that due to false negative results during putrefaction, it has to be interpreted carefully and it was suggested to use both EtG and EtS to be more accurate [104,105]. However, as EtG degradation and also possible artifactual formation both require microbial activity, VH is expected to be less prone to false positive and false negative EtG results [106][107].…”
Section: Alcohol and Drugsmentioning
confidence: 99%
“…Moreover, since EtS and EtG are formed via different pathways, either may be used to identify recent ethanol intake [38,[42][43][44][45][46].…”
Section: Ethyl Glucuronide and Ethyl Sulphatementioning
confidence: 99%
“…Baranowski et al [43] performed a study with in vitro experiments, in order to ascertain EtG and EtS degradation from bacterial colonies isolated from autopsy material (13 cases). Their results showed that EtG was completely degraded by bacteria with β-glucuronidase activity in a range of 3-4 days, whereas EtS was not affected by degradation within 11 days of incubation.…”
Section: Ethyl Glucuronide and Ethyl Sulphatementioning
confidence: 99%